Implementasi Artificial Intelligence dalam Proses Pembelajaran Mahasiswa Pendidikan Teknik Bangunan - Dwike Zaira Nurmila; Nabila Audya Asmaranti; Nazalya Noer Fadhilla; Zizzahrra Nanderis Lameikasya (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
The implementation of Artificial Intelligence (AI) is a significant concern in the development of learning systems, including the learning of Building Engineering Education students. This research aims to increase the effectiveness of learning for Building Engineering Education students. By using AI concepts and theories defined by John McCarthy, this research analyzes how AI becomes an important tool in creating a learning system that is more adaptive and responsive to student needs. The data collection technique used was a questionnaire to determine the results of the research. The results of this research show that respondents know AI and its role and the majority of respondents also feel helped by AI. AI also faces various challenges, such as further education to overcome various existing challenges by strengthening data security and increasing understanding of AI. Greater awareness and understanding of how AI can be used in education also deserves further attention.